2018
DOI: 10.13168/agg.2018.0017
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide tetrad effect in limestone: a tool to environment analysis of the Ruteh Formation, NW Iran.

Abstract: Exhibition of lanthanide tetrad effect in PAAS-normalized REE patterns, and non-CHARAC (non-CHArge-RAdius Control) behavior of Y/Ho and Zr/Hf in limestone of the Ruteh Formation, Kanigorgeh district (NW Iran), were studied in order to understand the reasons of occurrence of lanthanides tetrad effects. The computed values show that the third and fourth tetrads can be used as a good and powerful geochemical tool for investigation of physicochemical conditions of the depositional environment of the limestones. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…The high Sr and Mn contents in the concretions indicated the presence of hot and arid climatic features and were also related to the microbial mineralization of Mn and Sr ions (Tazaki and Morii, 2008). Some REE parameters such as the LREE/HREE, Eu/Eu*, and Ce/Ce* ratios can be used to elucidate the formation mechanisms of sedimentary rocks such as limestone (Abedini and Calagri, 2017;Abedini et al, 2018Abedini et al, , 2020Abedini and Khosravi, 2022). According to the curves of the REEs parameters in all samples (Figure 8), the total REE content, Eu/Eu*, Ce/Ce*, and LREE/HREE value differed significantly among points 11-13 in the core, points 2-10 in the body, and point 1 in the shell of the concretions.…”
Section: Discussionmentioning
confidence: 99%
“…The high Sr and Mn contents in the concretions indicated the presence of hot and arid climatic features and were also related to the microbial mineralization of Mn and Sr ions (Tazaki and Morii, 2008). Some REE parameters such as the LREE/HREE, Eu/Eu*, and Ce/Ce* ratios can be used to elucidate the formation mechanisms of sedimentary rocks such as limestone (Abedini and Calagri, 2017;Abedini et al, 2018Abedini et al, , 2020Abedini and Khosravi, 2022). According to the curves of the REEs parameters in all samples (Figure 8), the total REE content, Eu/Eu*, Ce/Ce*, and LREE/HREE value differed significantly among points 11-13 in the core, points 2-10 in the body, and point 1 in the shell of the concretions.…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions, the mineral phases precipitated from such solutions can produce negative Eu in mineral phases. Abedini et al (2016Abedini et al ( & 2019 suggested that a negative Eu anomaly can be attributed to low pH of fluids/solutions during geochemical processes.…”
Section: Zr/hfmentioning
confidence: 99%
“…Zr-Hf and Nb-Ta are known as geochemical pairs, also having similar charges and ionic radii, which are used as geochemical indicators to investigate the processes involved during the genesis of deposits. Despite the similar behavior of these geochemical pairs in geological environments, the variations of Y/Ho, Nb/Ta and Zr/Hf ratios (Table 3) are due to different factors such as fluids, solutions, mineral phases, fluid-rock interaction, ligands, complexation and the tetrad effect during the evolution of deposits (Minami et al, 1998;Spandler and Morris, 2016;Rezaei Azizi et al, 2017;Abedini et al, 2018c). Bau (1996) suggested that Y-Ho and Zr-Hf are mostly controlled by their ionic charge and radius (CHARAC) behavior during geochemical processes.…”
Section: Geochemical Constraints From Trace and Rare Earth Element DImentioning
confidence: 99%